Numerical analysis of water inﬁltration in an unsaturated residual soil by using the water retention curve - Carnero Carnero, Erasmo G. (2018)
The water infiltration analysis in soils is indispensable in order to understand how the moisture variations in the soil occurs in real situations as well as its influence in the engineering properties. However, such analysis requires the unsaturated soil parameters for the computations. These parameters, such as the unsaturated hydraulic conductivity can be estimated by using the soil water retention curve (SWRC). The SWRC governs the hydration and dehydration process in soils. The current research, studies the water infiltrations in a residual soil from Brazil under two unsaturated initial conditions. The analysis was performed by using a finite elements software employing the SWRC of the soil obtained experimentally. The results show that the saturation time is in function of the initial saturation of the soil and the quality of experimental data in the SWRC.